Pengembangan Instrumen Tes Standar Kognitif pada Mata Pelajaran IPA Kelas 7 SMP Di Kabupaten Banjar - Wardhani, Dyah Febria; Putra, Aminuddin Prahatama (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
The purpose of this study was to develop a standardized test instrument cognitive science subjects 7 junior class in accordance with steps of developing tests based on lattice UN year 2015/2016. Study Cognitive tests include the dimensions of factual knowledge, conceptual and procedural accordance with the revised Bloom cognitive levels. This type of research is the development of research. The data collection was done by using the test and non test. Source of data obtained from the results of the test answer sheets study, questionnaires and interviews with teachers and students in grade 7 junior in Banjar district. The sampling technique used purposive sampling and data analysis done qualitatively covering material, construction and language. Quantitative data analysis were performed using the MICROCAT Bigsteps 2:30 version. Results of the research is a description of the procedural process and product development are developed. The steps used to develop test instruments is to determine the purpose test, preparing test specifications, penulisansoal, a qualitative analysis by 9 experts (3 experts material, 3 experts construct, and 3 linguists), the revised phase I trials practicality in 4 teachers, a revised phase II, simulated use of the product in 3 students, the revision phase III, trial products on a single class of students from each school samples, analysis of items, and the revision stage IV. Learning achievement test instruments developed have excellent content validity based on the review of experts and high reliability butirsoal the 0.95. The end product development test research results in the form of 29 questions multiple choice test that can be used as a question bank and ready to be implemented.Keywords: Development of test instrument, Natural sciences, Junior high school, Kabupaten Banjar